Expansion, depression and collusion: The Belgian coal industry, 1901-1945 - Gil Montant (The Journal of European Economic History, 2020)
In the first half of the twentieth century a variety of factors - stagnant extraction processes, fierce competition from abroad, less favourable geological endowment, unstable demand during the interwar years - led Belgian coal producers to unify in order to preserve their production capacities. This paper takes the presence of massive coal imports in the Belgian market into account by using a three-equation theoretical model derived from industrial economics to assess the impact of the economic cycle on Belgian coal producers' market power within their domestic market. The results indicate that collusive strategies had a significant impact on the relationship between the economic cycle and the price-cost margin in the Belgian coal industry. In particular, the estimates do not contradict the findings of Haltiwanger and Harrington (1991).
Keywords: 330